Omega‐3 polyunsaturated fatty acids exert anti‐oxidant effects through the nuclear factor (erythroid‐derived 2)‐related factor 2 pathway in immortalized mouse Schwann cells. Issue 3 (13th October 2018) - Tatsumi, Yasuaki; Kato, Ayako; Sango, Kazunori; Himeno, Tatsuhito; Kondo, Masaki; Kato, Yoshiro; Kamiya, Hideki; Nakamura, Jiro; Kato, Koichi
Abstract: Aims/Introduction: Recent studies advocate that omega‐3 polyunsaturated fatty acids (ω‐3 PUFAs) have direct anti‐oxidative and anti‐inflammatory effects in the vasculature; however, the role of ω‐3 PUFAs in Schwann cells remains undetermined. Materials and methods: Immortalized mouse Schwann (IMS32) cells were incubated with the ω‐3 PUFAs docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA). The messenger ribonucleic acid levels of several anti‐oxidant enzymes (heme oxygenase‐1 [Ho‐1], nicotinamide adenine dinucleotide [phosphate] H quinone oxidoreductase 1, catalase, superoxide dismutase and glutathione peroxidase) were identified using real‐time reverse transcription polymerase chain reaction. Ho‐1 and nicotinamide adenine dinucleotide [phosphate] H quinone oxidoreductase 1 protein levels were evaluated using Western blotting. Nuclear factor (erythroid‐derived 2)‐related factor 2 (Nrf2) of the nuclear fraction was also quantified using western blotting. Catalase activity and glutathione content were determined by colorimetric assay kits. Nrf2 promoter‐luciferase activity was evaluated by a dual luciferase assay system. Results: Treatment with tert‐butyl hydroperoxide decreased cell viability dose‐dependently. DHA or EPA pretreatment significantly alleviated tert‐butyl hydroperoxide‐induced cytotoxicity. DHA or EPA increased the messenger ribonucleic acid levels of Ho‐1, nicotinamide adenine dinucleotide (phosphate) H quinone oxidoreductase 1 and catalase dose‐dependently. Ho‐1 protein level, catalase activity, Nrf2 promoter‐luciferase activity and intracellular glutathione content were significantly increased by DHA and EPA. Conclusions: These findings show that DHA and EPA can induce Ho‐1 and catalase through Nrf2, thus protecting Schwann cells against oxidative stress. ω‐3 PUFAs appear to exert their neuroprotective effect by increasing defense mechanisms against oxidative stress in diabetic neuropathies. Abstract : We demonstrated that both DHA and EPA could prevent cell death by inducing numerous antioxidants in IMS32 cells. Our findings suggest that enhancements of antioxidative defenses might have therapeutic value in the treatment of diabetic neuropathy.